(untitled) (Research, Society and Development, 2021)
The objective was to monitor the physiological performance of Sesbania virgata seeds (Cr. Pers) after different conditions and storage periods, with subsequent submission to dormancy overcoming treatments. The seeds were stored in uncontrolled conditions and in refrigerator for period 0; 35 and 70 days. After each storage period, five pre-germinative dormancy treatments were used, that is, control, immersion in sulfuric acid for 15 minutes, immersion in 20% caustic soda for 30 and 60 minutes and scarification with wooden sandpaper n°100. Subsequenthy, the following evaluations were carried out: seed water content, percentage, speed index and average germination time of both germination and emergence, electrical conductivity to assess integument rupture, length and dry mass of shoot and root system. The experimental design used was completely randomized, adopting a 2x3x5 factorial scheme (storage conditions x storage periods x pre-germination treatment). Mechanical scarification stood out in overcoming dormancy, the greater release of leachate was an indication of greater water absorption, which resulted in the triggering of the germination process. The storage in refrigerator favored the characteristics related to germination, while the uncontrolled environment resulted in the results for the emergency parameters. The storage for 70 days was the most favorable for conservation of seeds quality of yellow cambaí. In this way, it is suggested for future works the evaluation with longer storage periods, aiming at knowing to what extent the seeds can be stored without significant reduction in their quality. This work shows the seedling producer that sanding scarification is a simple and effective procedure to be used overcome dormancy, as well as indicating a satisfactory environment condition for the conservation of S. virgata.